Satire In Emma Healey’s Whistle In The Dark: Postmodern Study - Suciati, Aisyah Dewi; Hanifa, Siti (Program Studi Bahasa Inggris Universitas Trunojoyo Madura, 2021)
The aims of this study are to identify the social issues which are being satirized in Emma Healey’s Whistle in The Dark and and explicate Healey’s ways in satirizing the social issues in Whistle in The Dark. The writer applies the theory of satire in order to analyze social issues in the novel.This study applied qualitative research because the writer interpreted the novel in order to answer the research questions. The data are the narrator’s narration and characters’ utterances in the novel which are taken through scanning and skimming reading technique. The data analysis was done by classifying the narrations and utterances into the types of satire, discussing the findings, and concluding.The results of this study revealed that there are several social issues in the novel that are being satirized by Emma Healey, they are; environmental racism, mother-daughter relationship, queer issue, society’s fairytale, religious issue, technology in society, high-class society, society’s judgement, work and occupation, cyber pornography, sexual behaviour, people’s dissatisfaction, people’s anxiety, women’s insecurity, and teenager’s mental illness. The most used satire in the novel is Narrative.